(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the bustling and competitive landscape of the Indian hotel industry, the concept of job satisfaction has emerged as a pivotal factor influenced by the strategic implementation of Human Resources (HR) policies. As hotels strive to create a conducive work environment and deliver exceptional guest experiences, the role of HR policies in fostering job satisfaction among employees becomes crucial. These policies encompass a wide array of practices, including recruitment, training, compensation, performance management, and employee engagement, all of which collectively contribute to the overall well-being and contentment of the workforce. This paper aims to delve into the intricate relationship between HR policies and job satisfaction within the Indian hotel industry, unraveling the ways in which well-designed and effectively executed HR strategies can significantly impact employee morale, motivation, and overall job contentment.